On ϑ – Curvature Tensor of Finslerian Hypersurfaces Given by Generalised Kropina Type Metric - Miyan, Poonam; Pande, Hemlata; Thakur, Dhirendra (Nepal Journal of Mathematical Sciences, 2025)
The purpose of the present paper is to find angular metric tensor, carton torsion tensor, vcurvature tensor in a generalized Kropina space and the relation between v -curvatures with respect to Cartan connection CΓ of a Finsler space Fn = (Mn, L) and a Finsler space F*n = (Mn, L*) whose metric L* is derived from the metric L of Fn by L* (x, y) = μ1/2 (x, y) β1/2 (x, y), where μ1/2 (x, y) = (L1/2 + β1/2) (x, y) and β = bi(x) yi. The Finsler space F*n is called a generalized Kropina space under certain conditions.